Inbound marketing: análise das máquinas operadas pelas vinícolas do vale dos Vinhedos e da Campanha Gaúcha - Benetti, Jean Carlos (2022)
Adapting to changes is necessary to mitigate emerging business problems in the face of current business models. Working with Inbound Marketing contributes to this process. This relevance justifies the theme of this study, which aimed to analyze the Inbound Marketing practices operated by wineries in Vale dos Vinhedos and Campanha Gaúcha. It was supported by interviews guided by a script, prepared from a literature review, applied to those responsible for the marketing area of ​​wineries in both regions. Data collection was based on primary sources and the research design was qualitative and exploratory in nature. In total, considering the two regions, seven professionals were interviewed. The results indicated that wineries are seeking to update themselves in terms of marketing positioning; a process of transition to Inbound Marketing; This is not yet the priority model for most wineries; only one operates with the full format, which includes the Sales Funnel. Concomitantly with this context, the companies have already been working with Inbound Marketing tactics, gaining more engagement and acceptance from the online public. According to the respondents, the most effective tactics are those of social networks, especially Instagram, Facebook and WhatsApp. Finally, it is worth mentioning that this dissertation contributes in social, academic and empirical aspects, since the topic had not been studied in the context and in the delimited regions until now, and can help wineries and other companies that wish to work with Inbound Marketing.